Frontiers of Medical Micro/Nanorobotics: in vivo Applications and Commercialization Perspectives Toward Clinical Uses - Soto, Fernando; Chrostowski, Robert (Frontiers in Bioengineering and Biotechnology, 2018)
The field of medical micro/nanorobotics holds considerable promise for advancing medical diagnosis and treatment due to their unique ability to move and perform complex task at small scales. Nevertheless, the grand challenge of the field remains in its successful translation towards widespread patient use. We critically address the frontiers of the current methodologies for in vivo applications and discuss the current and foreseeable perspectives of their commercialization. Although no “killer application” that would catalyze rapid commercialization has yet emerged, recent engineering breakthroughs have led to the successful in vivo operation of medical micro/nanorobots. We also highlight how standardizing report summaries of micro/nanorobotics is essential not only for increasing the quality of research but also for minimizing investment risk in their potential commercialization. We review current patents and commercialization efforts based on emerging proof-of-concept applications. We expect to inspire future research efforts in the field of micro/nanorobotics toward future medical diagnosis and treatment.